MATHEMATICAL MODELS, OPERATIONS RESEARCH AND DECISION-MAKING METHODS IN LOGISTICS AND PRODUCTION PROCESSES - Савенко, Володимир; Нестеренко, Ірина; Клюєва, Вікторія; Полосенко, Олександр; Хапанцев, Ігор (SWorldJournal, 2024)
There are many models and concepts of system excellence. A comprehensive study of successful organisations in order to identify the fundamental concepts of their excellence is very important and valuable information for improving the overall production cu